2007
DOI: 10.1117/12.712093
|View full text |Cite
|
Sign up to set email alerts
|

Photoresist dissolution into a CO 2 compatible salt and CO 2 solution: investigation of processing conditions

Abstract: New lithographic techniques are being implemented to help further reduce feature sizes in microelectronics. A technique for the development of standard extreme ultraviolet (EUV) photoresists in a carbon dioxide compatible salt (CCS) and supercritical carbon dioxide (scCO 2 ) solution is being investigated to reduce line edge roughness and image collapse of high aspect ratio features. 1, 2 To understand the kinetics and overall mechanism of photoresist dissolution into the high pressure CCS/scCO 2 solution, a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…At the end of the experiment at ambient pressure, the mass fraction photoresist removed is nearly 100%. The discrepancy is due to remaining photoresist droplets on the rough SiO 2 surface, whose presence was verified using atomic force microscopy in previous work …”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…At the end of the experiment at ambient pressure, the mass fraction photoresist removed is nearly 100%. The discrepancy is due to remaining photoresist droplets on the rough SiO 2 surface, whose presence was verified using atomic force microscopy in previous work …”
Section: Resultssupporting
confidence: 52%
“…At this point the mass dependence on time is no longer linear due to the differing mechanism of photoresist droplet removal from the SiO 2 surface. The droplets are reduced in size and amount in experiments with wafer coupons using a hexamethyldisilazane (HMDS) adhesive coating as discussed in previous work . The bulk photoresist removal rate and not the droplet removal rate was the concentration of this paper.…”
Section: Resultsmentioning
confidence: 75%
“…Recently, several researchers have reported the ability to develop conventional polymeric resists in scCO 2 using cosolvents or tailored soluble additives. Mao et al have shown that the addition of selected cosolvents such as acetone or alcohols allows for the development of fluorinated and nonfluorinated photoresists in scCO 2 . , In addition, other researchers have shown that the inclusion of certain surfactants into scCO 2 imparts solubility to otherwise insoluble polymers …”
Section: Introductionmentioning
confidence: 99%